The Legend of the Old Man and the Packet of Jaffa Biscuits - Ivan Kovačević (University of Belgrade, 2016)
The urban legend that tells of how a young person ate by mistake some biscuits belonging to an old man sitting on the same bench in a Belgrade park is a transformation of an urban legend whose British version features an elderly British lady and a young immigrant, and which can be found throughout Europe, involving protagonists of various nationalities. Before undergoing transformation in Serbia, the legend was depoliticized, reducing the protagonists to two persons for the purposes of moral instruction and moral-religious propaganda. In Serbia, the age of the two protagonists has been reversed, while the moral of the story derives from the specific 1990s distinction between Slobodan Milošević’s Serbia and "the Other Serbia". In both cases, the legend propagates the idea of adaptation and assimilation, suggesting that "others" can learn to be like "us", which ensures that they are no longer in the position of "the other".